Uji Toksisitas Ekstrak methanol Beberapa Bagian Jaringan Tumbuhan Bayur (Pterospermum subpeltatum C.B. Rob) - Pince Salempa; Alfian Noor; Nunuk Hariani; Tjodi Harlim (Hasanuddin University, 2009)
Bayur plant (Pterospermum subpeltatum C.B. Rob) has not been searched for their secondary metabolites. However, this genes was used as traditional medicines such as Pterospermum javanicum as cure for dysentry, toothache and Pterospermum acerifolium fer itchy drug. From toxicity test by BLST upon various tissues it was found that methanol extract, compared to other parts, has higher value 220 ppm.Keywords: Pterospermum subpeltatum C.B. Rob, tocicity, traditional medicine, Artemia salina